The impact of moral injury on the wellbeing of UK military veterans - Victoria Williamson; Dominic Murphy; Sharon A. M. Stevelink; Shannon Allen; Edgar Jones; Neil Greenberg (BMC Psychology, 2021)
Abstract Background Experiences of potentially morally injurious events (PMIEs) have been found to negatively impact the mental health of US personnel/veterans, yet little is known about the effect of PMIEs on the mental health of the UK Armed Forces (AF). This cross-sectional study aimed to examine the association between PMIEs and the mental health outcomes of UK AF veterans. Method Assessments of PMIE exposure and self-report measures of common mental disorders were administered using an online questionnaire to 204 UK veterans. Subjects were classified as having experienced a morally injurious event (n = 66), a non-morally injurious traumatic event (n = 57), a ‘mixed’ event (n = 31), or no event (n = 50). Results Potentially morally injurious experiences were associated with adverse mental health outcomes, including likely anxiety disorders and suicidal ideation, compared to those who reported no event exposure. The likelihood of meeting criteria for probable PTSD was greatest in those who had experienced a non-morally injurious trauma. No statistically significant association between alcohol misuse and experiencing a PMIE or traumatic event was observed. Conclusions The results provide preliminary evidence that potentially morally injurious experiences are associated with adverse mental health outcomes in UK AF veterans. Further work is needed to better understand the interplay between morally injurious events and threat-based trauma in order to design effective pathways for prevention and intervention for people exposed to highly challenging events.